Retrospective analysis and materials of authors' researches of stomatological morbidity at the hyperfluorosis - A. K. Kucherenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The authors conducted retrospective analysis and study of materials of their own clinical researches of stomatological morbidity both of population of the ecologically adverse region and. workers of manufactures connected with fluorine outburst into environment. Analysis of stomatological morbidity was performed in two variations: 1) retrospective analysis of out-patient charts over 2000—2008; 2) analysis of own clinical observations over 2007—2010. 1245 out-patient charts of two groups (the first one — residents of Irkutsk, the second. — residents of Angarsk) were retrospectively analyzed. Depending on nosological form and. degree of manifestation of stomatological pathology all obtained material was divided in three main parts: teeth affection (I), pathology of tunica mucosa of mouth. (II) and. lesions of periodontium. (III). In population of the ecologically affected region (the second and. third groups) lesions of parodontium, were found to increase in numbers depending on duration of residence or length of work. At the same time in this category of patients we marked the increase of more generalized forms (generalized periodontitis, periodontosis) of affections. In the third group on the background of lessening of periodontitis and nidal periodontosis diagnostics there is growth of destructive-dystrophic changes in periodontium, the intensity of which is directly proportional to increasing of time of exposition of pathogenic factor. And, as a consequence, the number of more generalized forms of stomatological pathologies increases, which correspondingly demands working out and. introducing into practice up-to-date systems of treatment-diagnostic and. preventive measurements for this category of population.